Building solidarity through interruption in face-to-face interaction amongst Iranian men - Mohajer, Leila; Jariah Mohd. Jan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper investigates interruptions among upper middle-class Iranian men and the way they strategize and manipulate turns in face-to-face interaction. The recordings of informal conversations of these well acquainted men were transcribed and Beattie’s Interruption Model (1981) was adapted and applied as the framework of analysis. This study employed qualitative research design whereby natural-occurring conversation of participants from 15 participants from five groups, with each group comprising three participants, was recorded in the living room of one of the participants. The recorded conversations were transcribed according to an adapted version of Jefferson’s (1979) transcription convention and were qualitatively analysed. The transcribed data were analysed using Beattie’s interruption model (1981) and conversation analysis (CA) to examine the utterances and occurrences of interruptions based on turns being successful and complete at the time of interruptions. The findings of this study suggest that Iranian males interrupt each other cooperatively in order to show their support and solidarity. Although interruptions provide an opportunity for the interlocutors to dominate the interaction, there were no instances of dominance or any traces of intrusive behavior. In fact, the strategic use of interruptions denotes a collective effort to create in-group power that emphasizes solidarity amongst men in this study. This paper yields findings that go against stereotypical characteristics of men who exert power in their interactions. Such findings can be the result of the moderated patriarchal norms in Iranian society, which may have implications for studies on men’s interactional attitudes.